Sexual reproduction, sporophyte development and molecular variation in the model moss Physcomitrella patens: introducing the ecotype Reute. (25th March 2017) - Hiss, Manuel; Meyberg, Rabea; Westermann, Jens; Haas, Fabian B.; Schneider, Lucas; Schallenberg‐Rüdinger, Mareike; Ullrich, Kristian K.; Rensing, Stefan A.
Summary: Rich ecotype collections are used for several plant models to unravel the molecular causes of phenotypic differences, and to investigate the effects of environmental adaption and acclimation. For the model moss Physcomitrella patens collections of accessions are available, and have been used for phylogenetic and taxonomic studies, for example, but few have been investigated further for phenotypic differences. Here, we focus on the Reute accession and provide expression profiling and comparative developmental data for several stages of sporophyte development, as well as information on genetic variation via genomic sequencing. We analysed cross‐technology and cross‐laboratory data to define a confident set of 15 mature sporophyte‐specific genes. We find that the standard laboratory strain Gransden produces fewer sporophytes than Reute or Villersexel, although gametangia develop with the same time course and do not show evident morphological differences. Reute exhibits less genetic variation relative to Gransden than Villersexel, yet we found variation between Gransden and Reute in the expression profiles of several genes, as well as variation hot spots and genes that appear to evolve under positive Darwinian selection. We analyzed expression differences between the ecotypes for selected candidate genes in the GRAS transcription factor family, the chalcone synthase family and in genes involved in cell wall modification that are potentially related to phenotypic differences. We confirm that Reute is a P. patens ecotype, and suggest its use for reverse‐genetics studies that involve progression through the life cycle and multiple generations. Significance Statement: Although the moss Physcomitrella patens is an important evo‐devo model, most research to date has been conducted using the lab strain "Gransden". Here, we have carried out ecotype comparisons and introduce data for the ecotype "Reute", highlighting its utility for reverse genetics analyses of embryogenesis, sporophyte development and spore formation.